Identification of The Consequences of Covid-19 on Banking Credit - Hasan, Asriani; Risfan Rizaldi, Andi; Husna, Asmaul (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2022)
This study aims to look at the consequences of Covid-19 on bank credit, both from a positive and a negative side. This research is qualitative research with a descriptive method. The object of this research is Bank BTN Kajaolalido Makassar Branch. The data used in this research is primary data using interview techniques (interviews) with related parties at Bank BTN and observation. The data are in the form of credit planning, lending, and credit supervision. The results obtained in this study are the positive consequences of Covid-19 on bank credit, namely. Bank BTN Kajaolalido is increasingly aggressive in marketing various types of credit with lighter schemes. In addition, Bank BTN also provides credit relaxation such as assistance for the National Economic Acceleration or PEN in the form of interest subsidies and the provision of credit restructuring.